A rare case presentation of hydatid cyst in ilio-psoas muscle - Galani, Kamlesh; Trivedi, Bhargav; Vaghela, Jaivik (International Journal of Research in Medical Sciences, 2018)
We report a rare case of hydatid cyst in iliopsoas muscle in 35-year-old male patient. Where, patient presented with pain and swelling in right groin and fixed flexion deformity of right lower limb with constitutional symptoms. CECT abdomen revealed hydatis cyst with daughter cyst. We performed excision by retroperitoneal approach through lumber incision. Cyst was completely removed with daughter cysts.